2018
DOI: 10.3348/kjr.2018.19.4.767
|View full text |Cite
|
Sign up to set email alerts
|

Migraine with Aura: Surface-Based Analysis of the Cerebral Cortex with Magnetic Resonance Imaging

Abstract: ObjectivePrevious migraine studies have reported gray matter alterations in various cortical regions with conflicting results. This study aimed to explore a cortical morphometric difference in migraineurs with aura (MA) compared to healthy subjects (HS) and to delineate a possible difference between the cortical morphological features and different aura phenotypes.Materials and MethodsForty-eight MA and 30 HS that were balanced by sex, age, and educational level were selected for this study. T2-weighted and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 31 publications
3
53
4
Order By: Relevance
“…Migraine is a heterogeneous neurological disease. Some datasets only enrolled episodic migraineurs [12,15,16,22,[24][25][26]28], while some other datasets included both episodic and chronic migraineurs [13,14] or only chronic migraineurs [11,44]. Majority of the datasets (n = 14) in the CBMA included patients with mixed gender [10, 11, 13-17, 22, 25-28, 44], while two datasets only included female migraine patients [23,24] and one only male migraine patients [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine is a heterogeneous neurological disease. Some datasets only enrolled episodic migraineurs [12,15,16,22,[24][25][26]28], while some other datasets included both episodic and chronic migraineurs [13,14] or only chronic migraineurs [11,44]. Majority of the datasets (n = 14) in the CBMA included patients with mixed gender [10, 11, 13-17, 22, 25-28, 44], while two datasets only included female migraine patients [23,24] and one only male migraine patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the datasets (n = 14) in the CBMA included patients with mixed gender [10, 11, 13-17, 22, 25-28, 44], while two datasets only included female migraine patients [23,24] and one only male migraine patients [12]. Some datasets only included patients with aura [16,23,25,28] or without aura [13,22,[24][25][26], while some other studies included both patients with migraine without aura and with aura [10,11,15,17]. Individual CTh studies showed that the observed regional pattern of CTh abnormalities in patients with migraine was in uenced by age [10,11], gender [12], gender [12], disease duration [11, [13][14][15], attack frequency [13][14][15]44], pain intensity [14], the presence of aura [15][16][17], and photosensitivity [18].…”
Section: Discussionmentioning
confidence: 99%
“…In about one‐third of patients with migraine, a headache is accompanied or preceded by an aura . More than 90% of patients with migraine with auras have visual auras . Visual and ophthalmologic signs and symptoms are commonly reported by patients with migraine .…”
mentioning
confidence: 99%
“…M igraine is a chronic, paroxysmal, neurovascular primary headache that affects approximately 15% of people worldwide. 1,2 Although there are changes in cerebral vascular reactivity in the etiology of migraine, it is controversial. [3][4][5][6][7] There is evidence that systemic and cerebral circulation is affected by migraine.…”
mentioning
confidence: 99%
See 1 more Smart Citation